2020
DOI: 10.1097/mph.0000000000001536
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Children Treated for Infantile Hepatic Hemangioendothelioma

Abstract: Purpose: Infantile hepatic hemangioendothelioma (IHHE) is the most common hepatic vascular tumor in children. We report on the treatment outcome of our large single-center experience of patients with IHHE over a 9-year period. Materials and Methods: A retrospective analysis of all IHHE patients treated at the Children Cancer Hospital Egypt from April 2008 through April 2017. Results: In total, 28 patients (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 15 publications
1
20
0
2
Order By: Relevance
“…Our present case showed a high level of AFP, but the diagnosis of HCC was not taken into account, and the multiple hepatic tumors were considered as infantile hemangioendothelioma. Infantile hepatic hemangioendothelioma is the most common hepatic vascular tumor in children [ 12 ]. In a single-center experience of 28 cases, the median age at diagnosis was 3 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our present case showed a high level of AFP, but the diagnosis of HCC was not taken into account, and the multiple hepatic tumors were considered as infantile hemangioendothelioma. Infantile hepatic hemangioendothelioma is the most common hepatic vascular tumor in children [ 12 ]. In a single-center experience of 28 cases, the median age at diagnosis was 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen patients received drug treatment, nine of whom responded well to first-line propranolol/prednisolone, whereas seven patients needed salvage treatment. Twenty-five patients are alive, whereas three patients have died [ 12 ]. In 15 adult cases of hepatic epithelioid hemangioendothelioma who underwent hepatic resection or LT at our institution, no patient showed elevated AFP levels at all [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al [14] reported similar 5-year OS rates for EHE patients who underwent surgery, chemotherapy, embolization, or observation. Additionally, observation without treatment shows favorable outcomes in pediatric EHE cases [15]. However, definitive biomarkers of EHE aggressiveness have not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Basing on our own experience in adult patients treatment gained in oncology clinic and on pediatric literature regarding the role of the beta-adrenergic receptor blockade in low-aggressive vascular tumors (hemangioendothelioma epitheloides), 5,6 it was decided to administer the patient with 10 mg of propranolol three times a day. On cross section in the inner quadrants, a lesion 5 × 2.7 × 1.5 cm in diameter was visible, removed with a margin of adjacent tissues: the narrowest margin on the fascia side 2.5 cm wide, from the top 4.5 cm, from the bottom 3.5 cm.…”
Section: Bi-radsmentioning
confidence: 99%